Efeito da imunização pneumocócica pré-operatória na incidência de infecção respiratória no pós-operatório de cirurgia cardíaca - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Introduction: Pneumonia is among the main complications of cardiac surgeries, leading to increased mortality, length of stay and hospital costs. The 13-valent pneumococcal conjugate vaccine to prevent such occurrences has not yet been studied. Objective: To analyze if the incidence of respiratory infections in the postoperative period of cardiac surgeries is lower in patients immunized with the 13-valent pneumococcal conjugate vaccine. To study the main risk factors related to the development of infections in patients undergoing heart surgery. Methods: 40 patients were included in the study and randomized 1:1 to receive pneumococcal vaccine or placebo, 14 days before undergoing elective heart surgery. The incidence of infections in the 30 postoperative days was compared between the groups through calculations of mean, median and relative risk, through the tests Student's T test, Mann-Whitney, Fischer and Chi-square. Results: There were 6 respiratory infections in the vaccine group and 2 in the placebo group (p= 0.2024) and one death in the placebo group and none in the vaccine group (p= 0.3173). Chronic obstructive pulmonary disease (p= 0.003), diabetes mellitus (p=0,047) and peripheral arterial disease (p=0.0001) were related as risk factors for developing infections that generated increased length of stay (95% CI: 1.33- 7.13; p=0.0147) and postoperative ICU stay (95% CI: 1.87- 33.45; p= 0.0025). Conclusion: The application of pneumococcal vaccine 13v did not influence the development of postoperative pulmonary infections. Chronic obstructive pulmonary disease, diabetes mellitus and peripheral arterial disease were indicated as risk factors for the development of infections, increasing hospital stay and time in ICU.
Keywords: Pneumonia; Cirurgia torácica; Infecção respiratória; Infecção pneumocócica; Imunização; Vacina pneumocócica.; Pneumonia; Thoracic surgery; Respiratory infection; Pneumococcal infection; Immunization; Pneumococcal vaccine; CNPQ::CIENCIAS DA SAUDE